Optimalisasi Administrasi Engineering Untuk Mendukung Operasional Oakwood Hotel & Residence Surabaya - Zahra Putri Dwi Haryanti Rudyrtha; Rizky Dermawan (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Engineering administration plays an important role in supporting hotel operations through document management, procurement administration, inventory control, and maintenance coordination. This community service activity aimed to optimize engineering administration at Oakwood Hotel & Residence Surabaya through operational administrative assistance. The implementation method included direct assistance, observation, and active participation in preparing Purchase Requests (PR), inventory management, operational documentation, maintenance monitoring, and preparation of Fire Emergency Training materials. The results indicated that administrative assistance improved document organization, accelerated procurement administration, facilitated inventory control, and enhanced coordination among engineering personnel. In addition, participation in training material preparation contributed to improving employee preparedness and the effectivess of occupational safety programs. Therefore, optimizing engineering administration provided a positive contribution to improving operational effectiveness at Oakwood Hotel & Residence Surabaya.